Teknik Proyeksi Bisnis Forecasting Penjualan Menggunakan Metode Rata-Rata Trend di Storing Coffee Karawang - Ricko Naufal Zacky; Wahyudin Wahyudin; Syamsi Dhuha (Jurnal Serambi Engineering, 2023)
This research aims to determine the sales level of UMKM Storing Coffee in order to develop an appropriate marketing plan, thus increasing sales profitability. Forecasting is a technique used to predict future values using historical data. This research was conducted on a UMKM that specializes in Coffee beverages, namely Storing Coffee in Karawang city. This research was conducted by observing the sales forecasting analysis of coffee beverage products. The forecasting method used was an average with a trend analysis. Analysis was performed by comparing the smallest margin of error using the trend analysis method. Trend analysis is a technique used to determine the extent of fluctuations and factors that influence them. The profitability ratio is used to evaluate the effectiveness of business management. The higher the profitability ratio, the better because it means that the business owner obtains higher profits.